Pelatihan Digital Marketing dalam Meningkatkan Kompetensi Siswa SMK Negeri 1 Rantauprapat - Abdul Karim; Kusmanto Kusmanto; Mhd Bobbi Kurniawan Nasution; Sudi Suryadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The purpose of this training is to provide an understanding of digital marketing for students of SMK Negeri 1 Labuhanbatu Regency so that they have competence in the field of digital marketing and have an entrepreneurial spirit when they graduate from school. This training was created by utilizing Facebook as one of today's electronic marketing platforms. Facebook is one of the social media that is currently developing and can help in doing digital marketing (Digital Marketing). SMK Negeri 1 Labuhanbatu Regency is one of the schools that has an Online Business major. The activity method in its implementation uses various methods such as lectures, discussions, questions and answers, and provides training on Facebook pages. The results of the activity provide digital marketing training for students to become marketers and entrepreneurs.